War horse [videorecording (DVD)] - Spielberg, Steven, 1946-; Cumberbatch, Benedict, 1976-; Thewlis, David, 1963-; Watson, Emily, 1967-; Morpurgo, Michael (Touchstone Home Entertainment ; distributed by Buena Vista Home Entertainment, 2012)
Set against a sweeping canvas of rural England and Europe during the First World War, begins with the remarkable friendship between a horse named Joey and a young man called Albert, who tames and trains him. When they are forcefully parted, the film follows the extraordinary journey of the horse as he moves through the war, changing and inspiring the lives of all those he meets; British cavalry, German soldiers, and a French farmer and his granddaughter.